2007
DOI: 10.1002/ffj.1808
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil and antimicrobial activity of wild and cultivated Origanum vulgare L. subsp. hirtum (Link) letswaart from the Marmara region, Turkey

Abstract: The family Lamiaceae is represented by 45 genera, 546 species and 730 taxa in Turkey. The genus Origanum is represented in Turkey by 22 species; the ratio of endemism in the genus is 63%. Origanum vulgare subsp. hirtum collected from different localities in Marmara region and their cultivated forms provided by the Atatürk Central Horticultural Research Institute Yalova/Turkey were subjected to hydrodistillation to yield essential oils which were subsequently analysed by GC and GC-MS. The main constituents of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
0
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 24 publications
5
56
0
12
Order By: Relevance
“…3 Furthermore, geographic and climatic factors, such as duration of daylight and temperature, as well as cultivation factors, such as water stress and harvesting time, all affect the content of secondary metabolites in plants, including Origanum species. 2,10−14 For example, it has been shown that the development stage has a significant impact on the content and composition of both volatile terpenes and polyphenols in Greek oregano and that an optimal harvest time of aerial parts of the plant depends upon the secondary metabolites of interest.…”
Section: ■ Introductionmentioning
confidence: 99%
“…3 Furthermore, geographic and climatic factors, such as duration of daylight and temperature, as well as cultivation factors, such as water stress and harvesting time, all affect the content of secondary metabolites in plants, including Origanum species. 2,10−14 For example, it has been shown that the development stage has a significant impact on the content and composition of both volatile terpenes and polyphenols in Greek oregano and that an optimal harvest time of aerial parts of the plant depends upon the secondary metabolites of interest.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The antioxidant and other biological properties of the Origanum essential oils and extracts have recently been of great interest in both academia and food industries because of their antioxidant and antimicrobial potentials. Even though a few reports on the antimicrobial and antioxidant activities of the Origanum essential oils are available to date (Daferera et al, 2000;Esen et al, 2007;Busatta et al, 2008) …”
Section: Introductionmentioning
confidence: 99%
“…Daferera et al (2003) also reported that O. vulgare oil from Greece contains thymol (63.7%), pcymene (13.0%) and carvacrol (8.6%) as main components. These results indicate that Origanum plants are largely plentiful sources of thymol, carvacrol, -terpinene, and p-cymene (Esen et al, 2007;Kordali et al, 2008). Plant essential oils contain very complex natural mixtures or compounds at different concentrations and two or three components at fairly high concentrations (20 to 70%) as main components.…”
Section: Fumigant Toxicity Of Origanum Oil (O Vulgare)mentioning
confidence: 88%
“…They are also rich in bitter substances (Baytop, 1999;Esen et al, 2007). In vapor-phase toxicity bioassay using both closed and open container methods, the insecticidal activity of origanum oil against T. castaneum adults was higher in closed containers than in open containers indicating that the activity be exerted by fumigant action (Table 3).…”
Section: Fumigant Toxicity Of Origanum Oil (O Vulgare)mentioning
confidence: 99%